The analysis of factors influencing the motivation of subdistrict north padang high schoolers in following tuition classes program - Linda oktavianti; Yunia Wardi; Marwan Marwan (International Conferences on Educational, Social Sciences and Technology)
The aim of the research is to establish the factors that determine motivation of students in following tuition classes. The population of the studyinclude students of senior high school in subdistrict of North Padang. The sample of the study determined by using the area sampling method with 284 people as the respondent. The tool for analyzing data in this study is factor analysis. The result of the study shows there is a reduction from 20 to 19 variables in determine the motivation ofstudents who follow the tuition classes. Those 19 variables compose 4 main factors: (a) learning competition factors, (b) motivational learning support factors, (c) learning quality factors, (d) learning achievement factors. The trial of those variables has been tested by KMO and shows a number of 0,851 which mean it is include in satisfaction chategory.